Probing Polyoxometalate–Protein Interactions Using Molecular Dynamics Simulations. Issue 43 (17th August 2016) - Solé‐Daura, Albert; Goovaerts, Vincent; Stroobants, Karen; Absillis, Gregory; Jiménez‐Lozano, Pablo; Poblet, Josep M.; Hirst, Jonathan D.; Parac‐Vogt, Tatjana N.; Carbó, Jorge J.
Abstract: The molecular interactions between the Ce IV ‐substituted Keggin anion [PW11 O39 Ce(OH2 )4 ] 3− (CeK ) and hen egg‐white lysozyme (HEWL) were investigated by molecular dynamics simulations. The analysis ofCeK was compared with the Ce IV ‐substituted Keggin dimer [(PW11 O39 )2 Ce] 10− (CeK2 ) and the Zr IV ‐substituted Lindqvist anion [W5 O18 Zr(OH2 )(OH)] 3− (ZrL ) to understand how POM features such as shape, size, charge, or type of incorporated metal ion influence the POM⋅⋅⋅protein interactions. Simulations revealed two regions of the protein in which theCeK anion interacts strongly: cationic sites formed by Arg21 and by Arg45 and Arg68. The POMs chiefly interact with the side chains of the positively charged (arginines, lysines) and the polar uncharged residues (tyrosines, serines, aspargines) via electrostatic attraction and hydrogen bonding with the oxygen atoms of the POM framework. TheCeK anion shows higher protein affinity than theCeK2 andZrL anions, because it is less hydrophilic and it has the right size and shape for establishing interactions with several residues simultaneously. The larger, more negatively chargedCeK2 anion has a high solvent‐accessible surface, which is sub‐optimal for the interaction, while the smallerZrL anion is highly hydrophilic and cannot efficiently interact with several residues simultaneously. Abstract : The molecular interactions between polyoxometalates (POMs) and proteins can now be described at the atomic level by molecular dynamics simulations. How POM features, such as shape, size, charge, or type of incorporated metal influence these interactions, were investigated. The POM with a higher protein affinity is less hydrophilic and has the right shape for establishing interactions with several residues simultaneously.